P131 Respiratory abnormalities in a local cohort of patients with lysosomal storage disorders. (12th November 2019) - Shah, A; Devani, N; Hughes, D; Mandal, S
Abstract : Background: Lysosomal storage disorders (LSDs) encompasses a wide range of disorders which have a range of different respiratory manifestations including restrictive and obstructive lung defects, respiratory muscle weakness and sleep disordered breathing. A range of therapeutic options are available, from disease specific enzyme therapy to the use of non-invasive ventilation. 1 The Royal Free Hospital is a national centre for LSD patients and we sought to investigate the respiratory abnormalities in our local cohort. Method: Review of our local LSD patient cohort looking at respiratory physiology testing conducted in the last 2 years including spirometry assessment, sleep studies and respiratory muscle strength testing. Results: 53 patients with LSD were reviewed, (age 33.5± 13.4; 33% female; 74% Caucasian). There was a range of different disorders: Gauchers type 3 (21%); Pompe (32%); Mucopolysaccharidosis (MPS) I (26%); MPS II (10%) and MPS IV (11%). The overall data is summarised in table 1. Forty-four (83%) patients had had lung function in the last 2 years. Patients with MPS had a significantly reduced FEV1 and FVC compared to patients with Gauchers type 3. Seventy-five percent of patients had a sniff nasal inspiratory pressure (SNIP) test of which 25% had a SNIP of ≤40cmH2 O, with no significant difference amongst the groups. Thirty-six percent of patients had limited cardiorespiratory polysomnogrpahy, of which 69% had no evidence of sleep disordered breathing; 21% had mild obstructive sleep apnoea, 5% moderate and 5% severe. Conclusion: In our cohort of patients with LSD, those with MPS have a significant reduction in spirometry compared to Gauchers type 3. There were no differences between the groups in respiratory muscle strength or sleep study data, however, the number of patients who underwent sleep studies was fewer. The data highlights the importance of ensuring all patients with LSD undergo a thorough respiratory assessment and further highlights the need for further research into patients with LSD, respiratory manifestations and differences in the disorders. Reference: Faverio P, Stainer A, De Giacomi F, Gasperini S, Motta S, Canonico F, et al . Molecular pathways and respiratory involvement in lysosomal storage diseases. International Journal of Molecular Sciences 2019;20(2): 10.3390/ijms20020327.